Type XXVII collagen at the transition of cartilage to bone during skeletogenesis - Hjorten, Rebecca (2007)
COL27A1 is a member of the collagen fibrillar gene family and is expressed in cartilaginous tissues including the anlage of endochondral bone. To begin to understand its role in skeletogenesis, the temporospatial distributions of its RNA message and protein product, type XXVII collagen, were determined in developing human skeletal tissues. Laser capture microdissection and quantitative reverse-transcription polymerase chain reaction demonstrated that gene expression occurred throughout the growth plate, and that it was higher in the resting and proliferative zones than in hypertrophic cartilage. Immunohistochemical analyses showed that type XXVII collagen was most evident in hypertrophic cartilage at the primary ossification center and at the growth plate, and that it accumulated in the pericellular matrix. Synthesis of type XXVII collagen overlapped partly with that of type X collagen, a marker of chondrocyte hypertrophy, preceded the transition of cartilage to bone, and was associated with cartilage calcification. Immunogold electron microscopy of extracted ECM components from mouse growth plate showed that type XXVII collagen was a component of long non-banded fibrous structures, filamentous networks, and thin banded fibrils. The timing and location of synthesis suggest that type XXVII collagen plays a role during the calcification of cartilage and the transition of cartilage to bone.